EP3 Blockade Adds to the Effect of TP Deficiency in Alleviating Endothelial Dysfunction in Atherosclerotic Mouse Aortas - Hu, Chuangjia; Liu, Bin; Xu, Yineng; Wu, Xiangzhong; Guo, Tingting; Zhang, Yingzhan; Leng, Jing; Ge, Jiahui; Yu, Gang; Guo, Jinwei; Zhou, Yingbi (Frontiers in Physiology, 2019)
Endothelial dysfunction, which leads to ischemic events under atherosclerotic conditions, can be attenuated by antagonizing the thromboxane-prostanoid receptor (TP) that mediates the vasoconstrictor effect of prostanoids including prostacyclin (PGI2). This study aimed to determine whether antagonizing the E prostanoid receptor-3 (EP3; which can also be activated by PGI2) adds to the above effect of TP deficiency (TP–/–) under atherosclerotic conditions and if so, the underlying mechanism(s). Atherosclerosis was induced in ApoE–/– mice and those with ApoE–/– and TP–/–. Here, we show that in phenylephrine pre-contracted abdominal aortic rings with atherosclerotic lesions of ApoE–/–/TP–/– mice, although an increase of force (which was larger than that of non-atherosclerotic controls) evoked by the endothelial muscarinic agonist acetylcholine to blunt the concurrently activated relaxation in ApoE–/– counterparts was largely removed, the relaxation evoked by the agonist was still smaller than that of non-atherosclerotic TP–/– mice. EP3 antagonism not only increased the above relaxation, but also reversed the contractile response evoked by acetylcholine in NO synthase-inhibited atherosclerotic ApoE–/–/TP–/– rings into a relaxation sensitive to I prostanoid receptor antagonism. In ApoE–/– atherosclerotic vessels the expression of endothelial NO synthase was decreased, yet the production of PGI2 (which evokes contraction via both TP and EP3) evoked by acetylcholine was unaltered compared to non-atherosclerotic conditions. These results demonstrate that EP3 blockade adds to the effect of TP–/– in uncovering the dilator action of natively produced PGI2 to alleviate endothelial dysfunction in atherosclerotic conditions.